2022
DOI: 10.1063/5.0096395
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent droplet breakage in a von Kármán flow cell

Abstract: Droplet dispersion in liquid–liquid systems is a crucial step in many unit operations throughout the chemical, food, and pharmaceutic industries, where improper operation causes billions of dollars of loss annually. A theoretical background for the description of droplet breakup has been established, but many assumptions are still unconfirmed by experimental observations. In this investigation, a von Kármán swirling flow device was used to produce homogeneous, low-intensity turbulence suitable for carrying out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Several models consider dimensional units (Martinez-Bazan et al 2010;Qi et al 2020), complicating the comparisons between different configurations and missing some hidden controlling parameters, while empirical formula, with important assumptions in the models not rigorously verified, have been applied outside their initial fitting range (Tsouris & Tavlarides 1994;Andersson & Andersson 2006;Martinez-Bazan et al 2010). Recent computational work has investigated various aspects of the break-up of drops in turbulent flow, including long bubble lifetime near critical conditions and limits of the Hinze-scale concept (Vela-Martín & Avila 2022), the interaction of turbulence cascade and the break-up dynamics in steady-state turbulent emulsion configuration (Crialesi-Esposito et al 2022;Crialesi-Esposito, Chibbaro & Brandt 2023), while experimental work has discussed the role of small-scale eddies in bubble break-up (Qi et al 2022) or drop break-up in a von Kármán flow (Ravichandar et al 2022). Separately, atomization of jets has received considerable attention, with analysis of the subsequent instabilities controlling the scale selection, break-up and drop-size distribution (e.g.…”
Section: Context and Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…Several models consider dimensional units (Martinez-Bazan et al 2010;Qi et al 2020), complicating the comparisons between different configurations and missing some hidden controlling parameters, while empirical formula, with important assumptions in the models not rigorously verified, have been applied outside their initial fitting range (Tsouris & Tavlarides 1994;Andersson & Andersson 2006;Martinez-Bazan et al 2010). Recent computational work has investigated various aspects of the break-up of drops in turbulent flow, including long bubble lifetime near critical conditions and limits of the Hinze-scale concept (Vela-Martín & Avila 2022), the interaction of turbulence cascade and the break-up dynamics in steady-state turbulent emulsion configuration (Crialesi-Esposito et al 2022;Crialesi-Esposito, Chibbaro & Brandt 2023), while experimental work has discussed the role of small-scale eddies in bubble break-up (Qi et al 2022) or drop break-up in a von Kármán flow (Ravichandar et al 2022). Separately, atomization of jets has received considerable attention, with analysis of the subsequent instabilities controlling the scale selection, break-up and drop-size distribution (e.g.…”
Section: Context and Motivationmentioning
confidence: 99%
“…2022) or drop break-up in a von Kármán flow (Ravichandar et al. 2022). Separately, atomization of jets has received considerable attention, with analysis of the subsequent instabilities controlling the scale selection, break-up and drop-size distribution (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…To verify these models, a large number of experimental data on fluid particle breakage are required. Several studies have reported experiments of breakage frequency and DSD for bubble and drop, respectively 12,22–42 (summarized in Tables S3.1 and S3.2). Some experiments showed that the breakage frequency monotonically increased with increasing fluid particle size 12,23–30 .…”
Section: Introductionmentioning
confidence: 99%
“…Their experiment showed that the breakage frequency first increased to a maximum and then decreased when the drop size increased. Herø et al 32 and Ravinchandar et al 34 performed the experiments on drop breakage in a vertical channel and a Von Kármán flow, respectively. The measured breakage frequency also showed the similar non‐monotonic trend when drop size increased even in the relatively lower dissipation rates of turbulent kinetic energy (please see Table S3.1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation